2010
DOI: 10.1051/0004-6361/201014584
|View full text |Cite
|
Sign up to set email alerts
|

TheHerschelVirgo Cluster Survey

Abstract: We present a resolved dust analysis of three of the largest angular size spiral galaxies, NGC 4501 and NGC 4567/8, in the Herschel Virgo Cluster Survey (HeViCS) science demonstration field. Herschel has unprecedented spatial resolution at far-infrared wavelengths and with the PACS and SPIRE instruments samples both sides of the peak in the far infrared spectral energy distribution (SED). We present maps of dust temperature, dust mass, and gas-to-dust ratio, produced by fitting modified black bodies to the SED … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2010
2010
2013
2013

Publication Types

Select...
9

Relationship

7
2

Authors

Journals

citations
Cited by 45 publications
(22 citation statements)
references
References 23 publications
0
22
0
Order By: Relevance
“…If the 70-µm point is higher than our fit using 160, 250, 350 and 500 µm, this suggests a warmer component (i.e. Bendo et al 2010a;Smith et al 2010). We find that the SED fit overpredicts the 70-µm value over much of the galaxy.…”
Section: Temperature and Emissivitymentioning
confidence: 51%
See 1 more Smart Citation
“…If the 70-µm point is higher than our fit using 160, 250, 350 and 500 µm, this suggests a warmer component (i.e. Bendo et al 2010a;Smith et al 2010). We find that the SED fit overpredicts the 70-µm value over much of the galaxy.…”
Section: Temperature and Emissivitymentioning
confidence: 51%
“…The dust temperature is highest ahead of the dust mass surface density arms if we assume a trailing spiral structure rotating in the clockwise direction. Dust temperature and mass maps for NGC 4501 and NGC 4567/8 in the Herschel Virgo Cluster Survey have also shown that the peaks in dust temperature were not coincident with those in mass (Smith et al 2010). Fig.…”
Section: Distribution Of Dust Temperature and Massmentioning
confidence: 99%
“…excluding the 24 µm data point) using a single modified blackbody. This can be explained because there is a non-negligible contribution from the warm dust component to the Herschel PACS 70 µm flux density, as found for the integrated emission of other nearby galaxies (see, e.g., Bendo et al 2010;Smith et al 2010). However, the temperature of the warm component is not tightly constrained since varying the warm dust temperature by as much as ±4 K produces statistically similar good fits (χ 2 ≤ 2 χ 2 min ).…”
Section: Dust Propertiesmentioning
confidence: 80%
“…3, and fitting the resulting totals. Note that we tested the effect of removing the 70-µm data point from our SED fit to ensure that it was not forcing the curve to peak at shorter wavelengths and that it was not from a separate thermal component of the dust (Bendo et al 2010a(Bendo et al , 2012Smith et al 2010). We found that the 70-µm flux falls on the best-fitting curves within uncertainties for these tests, and thus we use all five wavelengths in our fitting routine.…”
Section: Sed Fittingmentioning
confidence: 99%